A new method of measuring the transepidermal water loss (TEWL) of dog skin - Yoshihara, T.(Kao Corp., Tokyo (Japan)); Shimada, K; Momoi, Y; Konno, K; Iwasaki, T (Journal of Veterinary Medical Science, 2007)
Human skin barrier function is evaluated by measuring transepidermal water loss (TEWL). However, this conventional method has not been applied to assess canine skin barrier function because the equipment is not suitable for dogs due to the effects of air turbulence resulting from movement of the subject and vapor from the subject's hair coat. The TEWL analyzer CC-01 was developed as a closed-chamber method device; this means that instead of using the open-chamber method, it has a ventilated chamber that uses dry air. TEWL values measured by CC-01 show less variability than those measured by the conventional method. An ambient temperature of 20-26 deg C is optimal for measurement with the CC-01, and humidity affects the length of measurement but not the values. The CC-01 may be more reliable for measurement of TEWL than the conventional methods and may give new insights in the evaluation of skin barrier function in dogs.